Development of a TaqMan® Allelic Discrimination qPCR Assay for Rapid Detection of Equine CXCL16 Allelic Variants Associated With the Establishment of Long-Term Equine Arteritis Virus Carrier State in Stallions - Thieulent, Come J.; Carossino, Mariano; Balasuriya, Udeni B. R.; Graves, Kathryn; Bailey, Ernest; Eberth, John; Canisso, Igor F.; Andrews, Frank M.; Keowen, Michael L.; Go, Yun Young (Frontiers in Genetics, 2022)
Equine arteritis virus (EAV) is the causative agent of equine viral arteritis (EVA), a respiratory, systemic, and reproductive disease of equids. Following natural infection, up to 70% of the infected stallions can remain persistently infected over 1 year (long-term persistent infection [LTPI]) and shed EAV in their semen. Thus, the LTP-infected stallions play a pivotal role in maintaining and perpetuating EAV in the equine population. Previous studies identified equine C-X-C motif chemokine ligand 16 (CXCL16) as a critical host cell factor determining LTPI in the stallion’s reproductive tract. Two alleles (CXCL16S and CXCL16r) were identified in the equine population and correlated with the susceptibility or resistance of a CD3+ T cell subpopulation in peripheral blood to in vitro EAV infection, respectively. Interestingly, CXCL16S has been linked to the establishment of LTPI in stallions, and thus, genotyping stallions based on CXCL16S/r would allow identification of those at the highest risk of establishing LTPI. Thus, we developed a TaqMan® allelic discrimination qPCR assay for the genotyping of the equine CXCL16 gene based on the identification of a single nucleotide polymorphism in position 1,073 based on NCBI gene ID: 100061442 (or position 527 based on Ensembl: ENSECAG00000018406.2) located in exon 2. One hundred and sixty horses from four breeds were screened for the CD3+ T cell susceptibility phenotype to EAV infection by flow cytometry and subsequently sequenced to determine CXCL16 allelic composition. Genotyping by Sanger sequencing determined that all horses with the resistant CD3+ T cell phenotype were homozygous for CXCL16r while horses with the susceptible CD3+ T cell phenotype carried at least one CXCL16S allele or homozygous for CXCL16S. In addition, genotypification with the TaqMan® allelic discrimination qPCR assay showed perfect agreement with Sanger sequencing and flow cytometric analysis. In conclusion, the new TaqMan® allelic discrimination genotyping qPCR assay can be used to screen prepubertal colts for the presence of the CXCL16 genotype. It is highly recommended that colts that carry the susceptible genotype (CXCL16 S/S or CXCL16S/r) are vaccinated against EAV after 6 months of age to prevent the establishment of LTPI carriers following possible natural infection with EAV.